A meta‐analysis of cardio‐metabolic abnormalities in drug naïve, first‐episode and multi‐episode patients with schizophrenia versus general population controls. Issue 3 (4th October 2013) - Vancampfort, Davy; Wampers, Martien; Mitchell, Alex J.; Correll, Christoph U.; De, Amber; Probst, Michel; De, Marc
<x xml:space="preserve">Abstract</x> A meta‐analysis was conducted to explore the risk for cardio‐metabolic abnormalities in drug naïve, first‐episode and multi‐episode patients with schizophrenia and age‐ and gender‐ or cohort‐matched general population controls. Our literature search generated 203 relevant studies, of which 136 were included. The final dataset comprised 185, 606 unique patients with schizophrenia, and 28 studies provided data for age‐ and gender‐matched or cohort‐matched general population controls (n=3, 898, 739). We found that multi‐episode patients with schizophrenia were at increased risk for abdominal obesity (OR=4.43; CI=2.52‐7.82; p<0.001), hypertension (OR=1.36; CI=1.21‐1.53; p<0.001), low high‐density lipoprotein cholesterol (OR=2.35; CI=1.78‐3.10; p<0.001), hypertriglyceridemia (OR=2.73; CI=1.95‐3.83; p<0.001), metabolic syndrome (OR=2.35; CI=1.68‐3.29; p<0.001), and diabetes (OR=1.99; CI=1.55‐2.54; p<0.001), compared to controls. Multi‐episode patients with schizophrenia were also at increased risk, compared to first‐episode (p<0.001) and drug‐naïve (p<0.001) patients, for the above abnormalities, with the exception of hypertension and diabetes. Our data provide further evidence supporting WPA recommendations on screening, follow‐up, health education and lifestyle changes in people with schizophrenia.